Integrasi Teks Budaya Lokal Maumere dalam Pembelajaran Bahasa Indonesia: Penguatan Literasi Akademik Berbasis Kearifan Lokal - Alfrida Dabura; Agustina Afrianti Paulina Rani; Fensiana Pada; Yeremias Bardi; Viktori Viktori; Constantinus Bajo Nanggo (STIKes Ibnu Sina Ajibarang, 2026)
Academic literacy is a crucial competence in Indonesian language learning as it supports the development of critical thinking, academic reading, and writing skills. However, Indonesian language instruction is often disconnected from students’ cultural backgrounds, resulting in less meaningful learning experiences. This study aims to describe the integration of Maumere local cultural texts in Indonesian language learning and to analyze their contribution to strengthening academic literacy based on local wisdom. This research employed a qualitative descriptive approach with a case study design. Data were collected through classroom observations, in-depth interviews with lecturers and students, and analysis of instructional documents. The findings reveal that Maumere local cultural texts were integrated through the use of folktales, traditional expressions, and reflective as well as argumentative writing tasks. This integration contributed to the improvement of students’ critical reading skills, academic argumentation, and reflective literacy. Moreover, local cultural texts functioned as pedagogical capital that bridged students’ cultural experiences with academic language practices. The study concludes that integrating Maumere local cultural texts strengthens academic literacy while affirming students’ cultural identity. Therefore, Indonesian language learning should adopt a contextual approach grounded in local wisdom.